APPLICATION OF COOPERATIVE MODEL IN IMPROVING STUDENTS' KNOWLEDGE ON THE MATERIAL OF PROPHET MUHAMMAD SAW'S EXAMPLE AND COMPASSION IN CLASS 1 OF SD NEGERI 4 BLANGPIDIE - Asma, Yulia (Jurnal Pendidikan Profesi Guru, 2025)
Islamic Religious Education (PAI) has an important role in shaping the character of students who believe and fear Allah SWT. One of the essential aspects in education is the example and understanding of the love of the Prophet Muhammad SAW. The example of the Prophet Muhammad SAW is clearly seen in his honest, trustworthy and loving personal life. However, sometimes in this learning process it is not well absorbed by students due to several factors, this material is often centered on lecture methods and monotonous so that students' interest in the material quickly gets bored. The purpose of this study is to improve the learning outcomes of grade 1 students of SD Negeri 4 Blangpidie in the subject of PAI through cooperative learning. The type of research uses classroom action research (PTK). Based on the results of the study, there are two stages, namely the stages of cycle I and cycle II. In the stage of cycle I, several students who were found had not reached the KKM, then the second cycle stage was carried out, the students succeeded in achieving completeness and success.